J&J Vegetables Wholesale Ordering System - Serena Ng Yen Xin,; Sulaiman, Rabatul Aduni (Applied Information Technology And Computer Science, 2025)
J&J Vegetables Marketing supplies fresh produce to various sectors. Currently, the company relies on phone calls and WhatsApp for orders, leading to inefficiencies, miscommunication, and disorganised data. The objectives of this project are to design and develop the J&J Vegetables Wholesale Ordering System using an object-oriented and web-based approach, followed by comprehensive system testing and user acceptance testing.  The project adopts the prototype methodology as its software development lifecycle model. The system is developed using Visual Studio Code, Laravel framework, PHP, MySQL, XAMPP, JavaScript, HTML and CSS, and is hosted on a web server to ensure accessibility across devices. It supports key user groups, including administrators, staff, drivers, and customers within Johor Bahru and surrounding areas. This user-friendly platform streamlines the ordering process, improves data management, reduces errors, enhances customer experience, and supports the company’s expansion into door-to-door delivery services.